Pengelolaan Anggaran Pendapatan dan Belanja Desa di Desa Patumbak Kampung Kecamatan Patumbak Kabupaten Deli Serdang pada Tahun 2022 - Gaol, Ayu Indah Lumban; Gaol, Manatap Berliana Lumban; Sinurat, Mangasa (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The current problems of village governments are caused by the lack of implementation of Permendagri No. 20 of 2018, which emphasizes transparency, accountability, participation, regularity, and budget discipline in village financial management. Challenges involve low human resources, institutional effectiveness, village revenue governance, and community services. The focus of this research is the management of APBDes, considering concerns about cases of embezzlement of Village Funds in Deli Serdang Regency, such as in Sugau, Tanjung Morawa B, and Salabulan villages, which caused significant losses to state finances. The type of research used is qualitative, by analyzing how the Village Budget is managed. The data obtained is in the form of primary data, which is obtained directly from the results of the researcher's interview with informants. The results showed that Patumbak Kampung Village had prepared a village income and expenditure budget in accordance with Permendagri No. 20 of 2018, but at the stage of APBDes management, namely the implementation stage of Patumbak Kampung Village was not fully in accordance with Permendagri No. 20 of 2018 or only 90% was in accordance with Permendagri No. 20 of 2018.